2011
DOI: 10.1257/aer.101.3.615
|View full text |Cite
|
Sign up to set email alerts
|

House Prices and Marital Stability

Abstract: We investigate the effect of house price changes on MSA-level divorce rates using data for 1991-2010 from the Current Population Survey and the Federal Housing Finance Agency. Our findings suggest that changing house prices significantly affect divorce rates, and that these effects are asymmetric with respect to housing gains versus losses. In addition, we find differential effects for groups that are more likely to be homeowners versus renters. Some of this evidence is consistent with homeowners being locked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 27 publications
(28 reference statements)
2
39
0
Order By: Relevance
“…Other studies have found that house prices have significant effects on educational choices (Lovenheim ; Lovenheim and Reynolds ) rates of childbirth (Lovenheim and Mumford ; Dettling and Kearney ), demand for long‐term care insurance (Davidoff ) and divorce (Farnham et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Other studies have found that house prices have significant effects on educational choices (Lovenheim ; Lovenheim and Reynolds ) rates of childbirth (Lovenheim and Mumford ; Dettling and Kearney ), demand for long‐term care insurance (Davidoff ) and divorce (Farnham et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…We estimate the causal effect of house prices on health on the assumption that the geographic variation in the strength and timing of house price movements is conditionally exogenous to individual health. Recently, a large literature has exploited this approach to show that house price movements are important for a range of household activity including household consumption and saving (Campbell and Cocco, 2007;Disney et al, 2010;Attanasio et al, 2009), indebtedness (Hurst and Stafford, 2004), educational choices (Lovenheim, 2011;Lovenheim and Reynolds, 2013) rates of childbirth (Lovenheim and Mumford, 2013;Dettling and Kearney, 2014), demand for long-term care insurance (Davidoff, 2010) and divorce (Farnham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…13 As Love (2010) points out, this assumption is consistent with most parents' expectations. 14 For college graduates, Farnham et al (2011) find that divorces are also affected by past house-price changes. In particular, when house prices fall, homeowners can get locked into their homes, which makes trading the home and getting divorced very costly.…”
Section: The Modelmentioning
confidence: 99%